Synthesis of Some γ-Picolinyl-1,2,4,5-Dithiadiazine and Their Antimicrobial Activity - Bhaskar, C.S.; Vidhale, N.N.; Berad, B.N. (Asian Journal of Chemistry, 2010)
3-Aryl/alkylimino-5-γ-picolinyl-5-phenylimino-1,2,4,5-dithiadiazines (V) have been synthesized following the interaction of phenylimino-chloromethane sulphenyl chloride (III) and 1-aryl/alkyl-4-γ-picolinyl thiosemicarbazides (II). The latter, in turn, have been prepared by the condensation of aryl/alkyl isothiocyanates (I) and isoniazid. The structures of all these compounds were established on the basis of elemental analysis, equivalent weight determination and IR and PMR spectral data. The synthesized compounds were assayed for their antimicrobial activity against gram-positive as well as gram-negative microorganisms such as E. coli, S. aureus, S. typhi, B. subtilis. A. aerogenes and B. megatherium.